A catalyst for the coordinated oxidation of CO and NH3 and a preparation method thereof

By forming molecular sieve, transition metal and precious metal coatings on the catalyst, combined with the support of cordierite support, the problem of coordinated removal of CO and NH3 in the prior art is solved, and efficient catalytic conversion efficiency is achieved.

CN119237000BActive Publication Date: 2025-04-01ANHUI ORIENTAL LICHUAN ENVIRONMENTAL PROTECTION TECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411773713.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-04-01
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove exhaust gases that exist in co-existing CO and NH3, and the catalyst has different redox properties and surface acidity requirements for the two gases, and there is a lack of catalysts for synergistic removal.

Method used

The catalyst is prepared by solution coating and impregnation method. The molecular sieve coating, transition metal coating and precious metal coating are formed by mixing and ball milling of molecular sieve, Al2O3 sol, CeO2 sol and deionized water. Combined with the support of cordierite support, the coordinated oxidation of CO and NH3 is achieved.

Benefits of technology

It realizes efficient synergistic oxidation of CO and NH3, improves the catalytic conversion efficiency of the catalyst, and has good practical application value and prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119237000B_ABST
    Figure CN119237000B_ABST
Patent Text Reader

Abstract

The present invention provides a catalyst for the coordinated oxidation of CO and NH3 and a preparation method thereof, comprising the following steps: (1) mixing molecular sieve, Al2O3 sol, CeO2 sol and deionized water, and ball milling to obtain molecular sieve slurry; (2) treating a carrier with nitric acid, drying, coating the molecular sieve slurry on the surface of the dried carrier, and then drying and calcining to obtain a carrier containing a molecular sieve coating; (3) immersing the carrier in a slurry containing a transition metal compound, and then drying and calcining to obtain a carrier containing a transition metal coating; (4) immersing the carrier in a slurry containing a noble metal compound, and then drying and calcining to obtain the catalyst for the coordinated oxidation of CO and NH3. The catalyst of the present invention has good catalytic conversion efficiency of CO and NH3, and has good practical application value and prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of catalysts, and in particular relates to a catalyst for the coordinated oxidation of CO and NH3 and a preparation method thereof. Background Art

[0002] As my country's requirements for air quality continue to increase, the emission control of CO and NH3 has gradually been put on the agenda. In industrial waste gas from industries such as steelmaking, aluminum making, and lime kilns, CO exists as a common waste gas component due to incomplete combustion of fuel, and NH3 also becomes a common waste gas component due to the problem of ammonia escape during low-temperature denitrification. At present, the mainstream method in this field is end-of-pipe treatment, among which catalytic oxidation is the main means. As the two most common gaseous pollutants after denitrification, if there is a catalyst that can efficiently remove them at the same time, it will greatly reduce the transformation and operating costs of the waste gas post-treatment process. However, CO and NH3 have strong competitive adsorption on the catalyst, and the removal of the two pollutants has inconsistent requirements for the redox properties and surface acidity of the catalyst. There is currently no report on a catalyst for the synergistic removal of the two gases. Therefore, there is an urgent need for the research and development of an integrated catalyst with the ability to synergistically catalytically oxidize CO and NH3. Summary of the invention

[0003] In view of this, the present invention aims to overcome the defects in the prior art and proposes a catalyst for the synergistic oxidation of CO and NH3 and a preparation method thereof.

[0004] To achieve the above object, the technical solution of the present invention is achieved as follows:

[0005] A method for preparing a catalyst for the coordinated oxidation of CO and NH3 comprises the following steps:

[0006] (1) Mixing molecular sieve, Al2O3 sol, CeO2 sol and deionized water, and ball milling to obtain molecular sieve slurry;

[0007] (2) treating the carrier with nitric acid and drying it, coating the molecular sieve slurry on the surface of the dried carrier, and then drying and calcining to obtain a carrier containing a molecular sieve coating;

[0008] (3) impregnating the carrier containing the molecular sieve coating into a slurry containing a transition metal compound, and then drying and calcining to obtain a carrier containing the transition metal coating;

[0009] (4) The carrier containing the transition metal coating is impregnated in a slurry containing a noble metal compound, and then dried and calcined to obtain the catalyst for the coordinated oxidation of CO and NH3.

[0010] Furthermore, the preparation method of the Al2O3 sol in the step (1) comprises the following steps: adding pseudo-boehmite to deionized water, and then slowly adding nitric acid thereto, and obtaining the Al2O3 sol after the solution is clarified; the mass concentration of the nitric acid is 10%; the solid-liquid ratio of the deionized water to the pseudo-boehmite and the nitric acid is 20mL:1-1.5g:0.6-1.4mL; the pore volume of the pseudo-boehmite is 0.4-0.8mL / g, and the sodium oxide content is ≤0.1%.

[0011] The pore volume of pseudo-boehmite is closely related to its ability to bind reactant molecules. An appropriate pore volume can increase the surface area of ​​pseudo-boehmite, and at the same time, it has an appropriate pore size, which plays a simple selection role for the molecules adsorbed on the surface. In the present invention, pseudo-boehmite with a pore volume of 0.4-0.8 mL / g is selected to enhance the catalytic activity of the catalyst.

[0012] The sodium oxide content of pseudo-boehmite is closely related to its colloidal solubility. Pseudo-boehmite with low sodium oxide content has a higher surface hydroxyl content, which is conducive to the dispersion of aluminum oxide in aluminum sol. Therefore, pseudo-boehmite with low sodium oxide content is conducive to the uniform distribution of aluminum elements on the catalyst surface in the molecular sieve coating.

[0013] Furthermore, the preparation method of CeO2 sol in the step (1) comprises the following steps: dissolving cerous nitrate in deionized water, adding ammonia water thereto and stirring, then quickly adding hydrogen peroxide solution thereto and continuing stirring, heating the obtained suspension, and slowly adding nitric acid to the suspension until the solution is clarified to obtain CeO2 sol; the mass concentration of the ammonia water is 10-25%; the mass concentration of the hydrogen peroxide solution is 10-30%; the mass concentration of the nitric acid is 10%; the solid-to-liquid ratio of the cerous nitrate, deionized water, ammonia water, hydrogen peroxide solution and nitric acid is 1-1.5g:20 mL:0.5 mL:5-10 mL:0.6-0.9mL; the temperature of the heating step is 40-60°C.

[0014] Furthermore, the solid-to-liquid ratio of the molecular sieve, Al2O3 sol, CeO2 sol and deionized water in the step (1) is 10g:5-2mL:4-1mL:40mL, and the molecular sieve is ZSM-5 molecular sieve; the ball milling step in the step (1) is performed for 200-240 min; the particle size of Al2O3 in the molecular sieve slurry in the step (1) is 1-4 nm, and the particle size of CeO2 is 1-4 nm.

[0015] Sufficient ball milling time can ensure that the particle size of Al2O3 and CeO2 in the sol is small and evenly distributed. The aluminum and cerium in the small-particle sol coating are evenly distributed and can fully contact with the reactants. In addition, the small and evenly distributed Al2O3 and CeO2 particles can make the coating surface smooth and stable, which can make the molecular sieve coating adhere to avoid falling off.

[0016] Furthermore, the carrier in step (2) is a cordierite carrier with a particle size of 46 mesh; the nitric acid treatment in step (2) is to use nitric acid to etch the cordierite carrier, then use deionized water to thoroughly wash it to neutrality, and finally dry it; the mass concentration of the nitric acid is 0.5-1%; the time of the soaking step is 15 minutes; the temperature of the drying step is 90-110°C; the temperature of the calcination step in step (2) is 400-600°C.

[0017] Preferably, the temperature of the calcination step in step (2) is 500°C.

[0018] The specific surface area of ​​the cordierite carrier after nitric acid treatment should be 100-110 m 2 / g. Acid treatment can adjust the surface properties and structure of cordierite carriers. One of the effects is to increase the specific surface area of ​​cordierite carriers. A suitable specific surface area of ​​cordierite carriers can increase the loading rate of active components, provide more active sites for the catalyst surface, and make it have a higher turnover frequency.

[0019] Furthermore, the transition metal compound in the slurry containing the transition metal compound in step (3) is a manganese-containing compound and / or a copper-containing compound; and the mass concentration of the transition metal in the slurry containing the transition metal compound in step (3) is 2.5-20%.

[0020] Preferably, the transition metal compound is at least one of KMnO4, Mn(NO3)2 or Cu(NO3)2.

[0021] When the transition metal compound is a manganese-containing compound, the mass concentration of manganese in the slurry containing the transition metal compound is 5-20%; when the transition metal compound is a copper-containing compound, the mass concentration of copper in the slurry containing the transition metal compound is 2.5-10%.

[0022] Furthermore, the time of the impregnation step in step (3) is 0.5-1 hour; the temperature of the drying step in step (3) is 90-110° C.; and the temperature of the calcination step in step (3) is 450-650° C.

[0023] Preferably, the temperature of the calcination step in step (3) is 550°C.

[0024] Furthermore, the precious metal compound in the slurry containing precious metal compounds in step (4) is a silver-containing compound and / or a platinum-containing compound; the mass concentration of precious metal in the slurry containing precious metal compounds in step (4) is 0.1-5%; preferably, the slurry containing precious metal compounds in step (4) is a solution containing Pt(NO3)2.

[0025] Preferably, the noble metal compound is AgNO3 or Pt(NO3)2.

[0026] When the precious metal compound is a silver-containing compound, the mass concentration of silver in the slurry containing the precious metal compound is 1-5%; when the precious metal compound is a platinum-containing compound, the mass concentration of platinum in the slurry containing the precious metal compound is 0.1-0.5%.

[0027] Furthermore, the time of the impregnation step in step (4) is 0.5-1 hour; the temperature of the drying step in step (4) is 90-110° C.; and the temperature of the calcination step in step (4) is 300-500° C.

[0028] Preferably, the temperature of the calcination step in step (4) is 400-500°C.

[0029] The weight gain ratio of the catalyst after loading all the coatings is 5-8% compared to the cordierite carrier after pretreatment. The weight gain ratio of the catalyst can indicate the loading amount of the active components in the coating, and the appropriate loading amount plays an important role in the activity of the catalyst. If the loading amount is too low, it may cause insufficient active sites, acid sites, and active oxygen content in the catalyst, resulting in low catalyst activity. Excessive loading has the risk of clogging the pores, reducing the specific surface area of ​​the catalyst, and even the coating falling off, which will make it difficult for the reactants to fully contact the catalyst to undergo catalytic oxidation reactions, and will also affect the catalytic activity of the catalyst.

[0030] A catalyst for the coordinated oxidation of CO and NH3 prepared by using the preparation method.

[0031] The catalyst for the synergistic oxidation of CO and NH3 described in the present invention mainly includes three parts: a molecular sieve coating, a transition metal coating and a noble metal coating. The molecular sieve in the molecular sieve coating has a high specific surface area and a good pore structure, which is conducive to the dispersion of active components on the catalyst surface and the diffusion of reaction gases. The abundant surface acid sites are conducive to improving the selectivity of NH3 oxidation to N2. The CeO2 in the composite sol has excellent oxygen storage and release capabilities, which is conducive to improving the oxidation ability of the catalyst to CO and NH3. At the same time, due to the Brønsted acid sites on the surface of CeO2, the selectivity of NH3 oxidation to N2 is improved. The Cu and Mn oxides in the transition metal coating improve the oxidation ability of the catalyst for CO and NH3 due to their flexible and adjustable valence states, abundant active oxygen species and the formation of spinel phases. The Cu site improves the selectivity of N2 in the catalytic oxidation reaction of NH3 through the synergistic effect with the molecular sieve carrier and Ag. Ag in the noble metal coating is the main active site for NH3 oxidation, and Pt provides the main active site for CO oxidation. By regulating the ratio of the carrier, the additive and the noble metal coating, the synergistic and efficient removal of the two gases is achieved to the greatest extent. In addition, the role of the cordierite carrier is to support and provide a pore structure. Its internal regular pore structure is conducive to the flow of reactants and products, thereby reducing the heat accumulation effect during the exothermic reaction.

[0032] Compared with the prior art, the present invention has the following advantages:

[0033] The catalyst for the coordinated oxidation of CO and NH3 described in the present invention uses a solution coating method to load a molecular sieve coating, which can ensure the uniform distribution and low shedding rate of the molecular sieve coating. The loaded molecular sieve coating can make the carrier have the high dispersion characteristics of the molecular sieve; and the transition metal coating and the noble metal coating are loaded by an impregnation method, which does not require the addition of an additional binder to effectively ensure that the various components of the catalyst are evenly dispersed on the surface of the carrier and in the pores of the carrier.

[0034] The molecular sieve in the molecular sieve coating of the catalyst for the synergistic oxidation of CO and NH3 described in the present invention has a high specific surface area and a good pore structure, which is beneficial to the dispersion of active components on the catalyst surface and the diffusion of reaction gases. The abundant surface acid sites are beneficial to improving the selectivity of NH3 oxidation to N2. The CeO2 in the composite sol has excellent oxygen storage and release capabilities, which is beneficial to improving the oxidation ability of the catalyst for CO and NH3. At the same time, since the CeO2 surface has Brønsted acid sites, the selectivity of NH3 oxidation to N2 is improved.

[0035] The Cu and Mn oxides in the transition metal coating of the catalyst for the coordinated oxidation of CO and NH3 described in the present invention improve the oxidation ability of the catalyst for CO and NH3 due to their flexible and adjustable valence states, rich active oxygen species and the formation of spinel phases.

[0036] In the precious metal coating of the catalyst for the synergistic oxidation of CO and NH3 described in the present invention, Ag is the main active site for NH3 oxidation, and Pt provides the main active site for CO oxidation. By regulating the ratio of the carrier, the additive and the precious metal coating, the synergistic and efficient removal of the two gases is achieved to the greatest extent.

[0037] There is interaction between the Ag of the noble metal coating, the ZSM-5 molecular sieve in the molecular sieve coating and the Cu of the transition metal coating of the catalyst for the coordinated oxidation of CO and NH3 described in the present invention, which can further improve the oxidation activity of NH3 and the selectivity of N2.

[0038] The catalyst for the coordinated oxidation of CO and NH3 described in the present invention has good catalytic conversion efficiency of CO and NH3, and has good practical application value and prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is a test graph of the catalytic oxidation activity of the catalyst described in Example 1 of the present invention to CO;

[0040] Figure 2 This is a test graph of the catalytic oxidation activity of the catalyst described in Example 1 of the present invention to NH3;

[0041] Figure 3 This is a test graph of the N2 selectivity of the catalyst described in Example 1 of the present invention for catalytic oxidation of NH3. DETAILED DESCRIPTION

[0042] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.

[0043] The preparation method of the Al2O3 sol used in each embodiment of the present invention and each comparative example comprises the following steps:

[0044] 7 g of pseudo-boehmite was added to 100 mL of deionized water, and then 4 mL of 10% nitric acid was slowly added thereto. After the solution was clarified, Al2O3 sol was obtained.

[0045] The preparation method of the CeO2 sol used in each embodiment of the present invention and each comparative example comprises the following steps:

[0046] Dissolve 7.5 g of cerous nitrate in 100 mL of deionized water, add 2.5 mL of 25% ammonia water and stir, then quickly add 25 mL of 30% hydrogen peroxide solution and continue stirring, heat the obtained suspension at 50°C, and slowly add 4 mL of 10% nitric acid to the suspension until the solution becomes clear, thereby obtaining CeO2 sol.

[0047] The present invention will be described in detail below with reference to the embodiments.

[0048] Example 1

[0049] A method for preparing a catalyst for the coordinated oxidation of CO and NH3 comprises the following steps:

[0050] 1) Molecular sieve, Al2O3 sol, CeO2 sol and deionized water were mixed at a solid-liquid ratio of 10 g:5 mL:4 mL:40 mL and ball-milled for 8 h to obtain a slurry.

[0051] 2) Soak the cordierite carrier in 1% nitric acid for 15 minutes, then wash it thoroughly with deionized water until it is neutral, and finally dry it at 90°C;

[0052] 3) The dried cordierite carrier (46 mesh, length × width × height = 15 cm × 15 cm × 20 cm) was evenly coated with the slurry containing the molecular sieve and the composite sol, and then the residual liquid on the inner and outer walls of the cordierite was purged, and then placed in a drying equipment for drying at 90 ° C for 1 h;

[0053] 4) placing the carrier obtained in step 3) in a muffle furnace and calcining at 500 °C for 4 h at a heating rate of 5 °C / min in a dry air atmosphere to obtain a catalyst;

[0054] 5) The catalyst obtained in step 4) was immersed in a mixed solution of KMnO4 with a Mn mass concentration of 15% and Cu(NO3)2 with a Cu mass concentration of 10% for 10 min, and then the residual liquid on the inner and outer walls of the cordierite was purged, and then placed in a drying equipment for rapid drying to obtain a carrier, and the time was 10 min;

[0055] 6) placing the carrier obtained in step 5) in a muffle furnace and calcining at 550 °C for 4 h at a heating rate of 5 °C / min in a dry air atmosphere to obtain a catalyst;

[0056] 7) The catalyst obtained in step 6) was immersed in a mixed solution of AgNO3 with an Ag mass concentration of 5% and Pt(NO3)2 with a Pt mass concentration of 5% for 10 min, and then the residual liquid on the inner and outer walls of the cordierite was purged, and then placed in a drying equipment for rapid drying to obtain a carrier, and the time was 10 min;

[0057] 8) The catalyst obtained in step 7) is placed in a muffle furnace and calcined at 400 °C for 4 h with a heating rate of 5 °C / min. After calcination and cooling, a catalyst for the synergistic oxidation of CO and NH3 is obtained.

[0058] Example 2

[0059] The only difference from Example 1 is that in step 1), the solid-liquid ratio of molecular sieve, Al2O3 sol, CeO2 sol and deionized water is 10 g:5 mL:1 mL:40 mL.

[0060] Example 3

[0061] The only difference from Example 1 is that in step 1), the solid-liquid ratio of molecular sieve, Al2O3 sol, CeO2 sol and deionized water is 10 g:2 mL:4 mL:40 mL.

[0062] Example 4

[0063] The only difference from Example 1 is that the Mn mass concentration of the KMnO4 solution in step 4) is 5%.

[0064] Example 5

[0065] The only difference from Example 1 is that the Cu mass concentration of the Cu(NO3)2 solution in step 4) is 2.5%.

[0066] Example 6

[0067] The only difference from Example 1 is that the Ag mass concentration of the AgNO3 solution in step 6) is 1%.

[0068] Example 7

[0069] The only difference from Example 1 is that the Pt mass concentration of the Pt(NO3)2 solution in step 6) is 0.1%.

[0070] Comparative Example 1

[0071] The only difference from Example 1 is that in step 1), the molecular sieve, Al2O3 sol, and deionized water are in a solid-liquid ratio of 10 g:5 mL:40 mL, and CeO2 sol is not added.

[0072] Comparative Example 2

[0073] The only difference from Example 1 is that in step 1), the molecular sieve, CeO2 sol and deionized water are in a solid-liquid ratio of 10 g:4 mL:40 mL, and no Al2O3 sol is added.

[0074] Comparative Example 3

[0075] The only difference from Example 1 is that a Mn(NO3)2 solution with a Mn mass concentration of 15% is used in step 5).

[0076] Comparative Example 4

[0077] The only difference from Example 1 is that no Cu(NO3)2 solution is added in step 5).

[0078] Comparative Example 5

[0079] The only difference from Example 1 is that no KMnO4 solution is added in step 5).

[0080] Comparative Example 6

[0081] The only difference from Example 1 is that no Pt(NO3)2 solution is added in step 7).

[0082] Comparative Example 7

[0083] The only difference from Example 1 is that no AgNO3 solution is added in step 7).

[0084] The catalysts prepared in each embodiment and each comparative example were subjected to fixed bed reaction, with NH3 concentration of 500 ppm, CO concentration of 5000 ppm, O2 concentration of 10 vol.%, N2 as balance gas, and gas space velocity of 20000 h -1 , reaction temperature: 280 °C. Under this condition, the catalyst activity test was carried out, and the test results for CO are shown in Table 1.

[0085] Table 1 Catalyst activity test results

[0086]

[0087] As shown in Table 1, by comparing Examples 1-3, it can be found that the components in the molecular sieve coating have an improvement effect on the three properties of the catalyst's CO conversion rate, NH3 conversion rate, and N2 selectivity, and the performance is best when the molecular sieve, Al2O3 sol, CeO2 sol and deionized water are in a solid-liquid ratio of 10g:5mL:4mL:40mL. Combined with Example 1 and Comparative Example 1, the main contribution of CeO2 sol is to improve the CO conversion rate of the catalyst. Combined with Example 1 and Comparative Example 2, the main contribution of Al2O3 sol is to improve the NH3 conversion rate of the catalyst. Combined with Example 1, Example 4, Comparative Example 3, and Comparative Example 5, the main role of Mn in the transition metal coating is to improve the conversion rate of the catalyst to two target pollutants. The improvement effect increases with the increase of Mn concentration within a certain concentration range, and the effect of using KMnO4 as a Mn source is better than using Mn(NO3)2. Combined with the analysis of Example 1, Example 5, and Comparative Example 4, the main function of Cu in the transition metal coating is to improve N2 selectivity, and the improvement effect increases with the increase of Mn concentration within a certain concentration range. Combined with the analysis of Example 1, Example 6, and Comparative Example 6, the main function of Pt in the transition metal coating is to improve CO conversion rate. Combined with the analysis of Example 1, Example 7, and Comparative Example 7, the main function of Ag in the transition metal coating is to improve NH3 conversion rate.

[0088] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a catalyst for the coordinated oxidation of CO and NH3, characterized in that: The steps include: (1) Mixing molecular sieve, Al2O3 sol, CeO2 sol and deionized water, and ball milling to obtain molecular sieve slurry; (2) treating the carrier with nitric acid and drying it, coating the molecular sieve slurry on the surface of the dried carrier, and then drying and calcining to obtain a carrier containing a molecular sieve coating; (3) impregnating the carrier containing the molecular sieve coating into a slurry of a transition metal compound containing a manganese compound and a copper compound, and then drying and calcining to obtain a carrier containing the transition metal coating; (4) impregnating the carrier containing the transition metal coating into a slurry of a precious metal compound containing a silver compound and a platinum compound, and then drying and calcining to obtain the catalyst for the coordinated oxidation of CO and NH3; The preparation method of the Al2O3 sol in the step (1) comprises the following steps: adding pseudo-boehmite to deionized water, and then slowly adding nitric acid thereto, and obtaining the Al2O3 sol after the solution is clarified; the mass concentration of the nitric acid is 10%; the solid-liquid ratio of the deionized water to the pseudo-boehmite and the nitric acid is 20mL:1-1.5g:0.6-1.4mL; the pore volume of the pseudo-boehmite is 0.4-0.8mL / g, and the sodium oxide content is ≤0.1%; The solid-to-liquid ratio of the molecular sieve, Al2O3 sol, CeO2 sol and deionized water in step (1) is 10g:5-2mL:4-1mL:40mL, and the molecular sieve is ZSM-5 molecular sieve; the ball milling step in step (1) is performed for 200-240min; the particle size of Al2O3 in the molecular sieve slurry in step (1) is 1-4 nm, and the particle size of CeO2 is 1-4 nm; The carrier in step (2) is a cordierite carrier with a particle size of 46 mesh; the nitric acid treatment in step (2) is to use nitric acid to etch the cordierite carrier, then use deionized water to thoroughly wash it to neutrality, and finally dry it; the mass concentration of the nitric acid is 0.5-1%; the time of the soaking step is 15 minutes; the temperature of the drying step is 90-110°C; the temperature of the calcination step in step (2) is 400-600°C; The weight gain ratio of the catalyst after loading all the coatings is 5-8% compared with the weight gain ratio of the pre-treated cordierite carrier.

2. The method for preparing a catalyst for the synergistic oxidation of CO and NH3 according to claim 1, characterized in that: The preparation method of CeO2 sol in the step (1) comprises the following steps: dissolving cerous nitrate in deionized water, adding ammonia water thereto and stirring, then quickly adding hydrogen peroxide solution thereto and continuing stirring, heating the obtained suspension, and slowly adding nitric acid to the suspension until the solution is clarified to obtain CeO2 sol; the mass concentration of the ammonia water is 10-25%; the mass concentration of the hydrogen peroxide solution is 10-30%; the mass concentration of the nitric acid is 10%; the solid-to-liquid ratio of the cerous nitrate, deionized water, ammonia water, hydrogen peroxide solution and nitric acid is 1-1.5g:20 mL:0.5 mL:5-10mL:0.6-0.9mL; the temperature of the heating step is 40-60°C.

3. The method for preparing a catalyst for the coordinated oxidation of CO and NH3 according to claim 1, characterized in that: The mass concentration of transition metal in the slurry containing transition metal compound in step (3) is 2.5-20%.

4. The method for preparing a catalyst for the coordinated oxidation of CO and NH3 according to claim 3, characterized in that: The time of the impregnation step in the step (3) is 0.5-1 hour; the temperature of the drying step in the step (3) is 90-110° C.; the temperature of the calcination step in the step (3) is 450-650° C.

5. The method for preparing a catalyst for the synergistic oxidation of CO and NH3 according to claim 1, characterized in that: The mass concentration of the precious metal in the slurry containing the precious metal compound in step (4) is 0.1-5%.

6. The method for preparing a catalyst for the coordinated oxidation of CO and NH3 according to claim 5, characterized in that: The slurry containing precious metal compounds in step (4) is a solution containing Pt(NO3)2.

7. The method for preparing a catalyst for the synergistic oxidation of CO and NH3 according to claim 5, characterized in that: The time of the impregnation step in the step (4) is 0.5-1 hour; the temperature of the drying step in the step (4) is 90-110° C.; the temperature of the calcination step in the step (4) is 300-500° C.

8. A catalyst for the synergistic oxidation of CO and NH3 prepared by the preparation method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Silver-containing normal-temperature monolithic catalyst for carbon monoxide and preparation method thereof

    CN103170348A

  • Rare earth ore monolithic catalyst and preparation method and application thereof

    CN109939689A

  • Exhaust treatment system for a lean burn engine

    CN112955244A